2017
DOI: 10.5455/apd.266148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of obesity on self-respect and sexuality in women

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…37 In another study, which is similar to ours and conducted with 184 women in our country, it is stated that sexual satisfaction increases as body perception improves. 38 In a study conducted with obese people with a BMI above 40, it was found that those with low body perception had low sexual satisfaction. 13 It is anticipated that once obese individuals are down to their ideal weight, their body perception scores will also change, also affecting the score obtained from sexual experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 In another study, which is similar to ours and conducted with 184 women in our country, it is stated that sexual satisfaction increases as body perception improves. 38 In a study conducted with obese people with a BMI above 40, it was found that those with low body perception had low sexual satisfaction. 13 It is anticipated that once obese individuals are down to their ideal weight, their body perception scores will also change, also affecting the score obtained from sexual experiences.…”
Section: Discussionmentioning
confidence: 99%
“…43 In a study conducted on obese women, a decrease in body perception and sexual satisfaction was found, and it was concluded that self-esteem affects sexual life. 38 In a study examining sexuality after weight loss five years after bariatric surgery, improvement in sexual activity was observed in both genders. 44 The findings of our study that obese individuals have low body perception, and that sexuality is affected, as a result, are similar to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has also been stated that obesity has negative effects on sexual functioning. 6,7 On the other hand, Küçük et al 5 found that the sexual satisfaction of obese individuals was high.…”
Section: Discussionmentioning
confidence: 99%
“…The way an individual perceives his body affects his relationship with his body and self. Although many people think that body image has little effect on their lives, actually people's feelings and thoughts about their bodies are attitudes towards life [12]. Body image; It is shaped by the individual's values, personality, and relationships with his environment.…”
Section: Body Imagementioning
confidence: 99%